Comparative assessment of human salivary α-amylase inhibitor from Indonesian herbs - Khomaini Hasan; Angga Himas Setyawan; Muhamad Abidin; Nurul Aida Fathya; Dewi Ratih Handayani; Desy Linasari; Saronom Silaban; Toto Subroto; Muhammad Yusuf (Jurnal Pendidikan Kimia (JPKIM), 2023)
Diabetes mellitus (DM) is a multifactorial disease defined by persistent hyperglycemia and impaired carbohydrate, lipid, and protein metabolism due to a lack of insulin secretion. The objective of this study was to assess the Indonesian herbs which have the ability to act as human salivary α-amylase inhibitors, thus, that they can be implemented for medical purposes. In this study, fifteen Indonesian herbs were assessed for their capability as α-amylase inhibitor. The water-reflux method was used to extract all potential water-soluble active components. The Fuwa technique was used to test α-amylase activity. There were significant variations in the effects of herbs on salivary α-amylase activity, according to the statistical using one-way ANOVA and Post Hoc Tukey between the with and without inhibitors. According to the findings, Turmeric (Curcuma longa L.) and pandan leaf (Pandanus amaryllifolius Roxb) had the highest inhibitory power (80%).Keywords: Diabetes mellitus; Flavonoids; Herbs; α-amylase inhibitors